Stagnation point flow of non-newtonian nanofluids with active and passive controls of nanoparticles / Nadhirah Abdul Halim - Nadhirah , Abdul Halim (2019)
In this thesis, newly upgraded non-Newtonian nanofluids models near a stagnation point are proposed under the influence of active and passive controls of the nanoparticles. These boundary layer fluid flows considered Maxwell, Williamson, second-grade, Carreau and Powell-Eyring non-Newtonian fluids. The flows are represented by the conventional partial differential equations in fluid dynamics added with unique expression of stress tensor in the momentum equation which satisfy the continuity equation for conservation of mass. The Buongiorno’s model is used as a base model in this analysis as it takes into consideration the effect of Brownian motion and thermophoresis of the nanoparticles in the energy and mass transport equations of the flows. All these equations are reduced into a set of simpler partial differential equations via boundary layer approximation. The governing equations are later converted to a set of nonlinear ordinary differential equations by using similarity transformation. Shooting technique is employed to reduce these resulting equations into a set of boundary value problem in the form of nonlinear first order ordinary differential equations subject to the specific initial and boundary conditions which reflect the effect of active and passive controls of the nanoparticles in two different occasions. The bvp4c function, developed based on finite difference method by MATLAB is utilized to further solve the newly upgraded Maxwell, Williamson, Carreau and Powell-Eyring models while the BVPh 2.0 package in Mathematica is employed to solve the newly upgraded second grade nanofluids flow model. The effects of active and passive controls of the nanoparticles are compared graphically and tabularly. The influences of other considered parameters towards the flow profiles are also presented while the numerical values of skin friction coefficient, Nusselt number and Sherwood number are listed. The stagnation parameter increases the heat transfer of all the non-Newtonian nanofluids flows studied. Furthermore, the heat transfer rate of the boundary layer flows under passive control of nanoparticles is consistently higher in magnitude as compared to the ones under active control of nanoparticles.